Complex care needs of patients with late-stage HIV disease: A retrospective study - Halman, Mark (AIDS Care, 2013)
This retrospective chart review provides a profile of an emerging population of vulnerable HIV patients with complex comorbidities. Data were abstracted from all 87 patients admitted in 2008 to Casey House, a community-based hospital dedicated to supportive and palliative care for persons with HIV in Toronto, Canada. We describe patient characteristics, including medical and psychiatric conditions, and use a Venn diagram and case study to illustrate the frequency and reality of co-occurring conditions that contribute to the complexity of patients’ health and health care needs. The mean age at admission was 48.9 years (SD = 10.5). Eighty percent were male. Patients experienced a mean of 5.8 medical comorbidities (SD = 2.3) and 1.9 psychiatric disorders (lifetime axis I diagnoses). Forty-one patients (47%) experienced cognitive impairment including HIV-associated dementia. Patients were on a mean of 11.8 (SD = 5.3) medications at admission; 74% were on antiretroviral medications with 55% reporting full adherence. Current alcohol and drug use was common with 54% reporting active use at admission. Our Venn diagram illustrates the breadth of complexity in the clients with 9% of clients living in unstable housing with three or more medical comorbidites and two or more psychiatric diagnoses. Comprehensive HIV program planning should include interventions that can flexibly adapt to meet the multidimensional and complex needs of this segment of patients. Researchers, policymakers and clinicians need to have greater awareness of overlapping medical, psychiatric and psychosocial comorbidities. Inclusion of the needs of these most vulnerable patients in the development of evidence based guidelines is an important step for effectively treating, preventing and planning for the future of HIV/AIDS care.